Thermo-responsive hydrogel-supported antibacterial material with persistent photocatalytic activity for continuous sterilization and wound healing. (15th January 2022) - Liu, Lin; Shi, Junpeng; Sun, Xia; Zhang, Yongqu; Qin, Jingwang; Peng, Shanshan; Xu, Jixuan; Song, Liang; Zhang, Yun
Abstract: Antibacterial photocatalytic therapy (APCT) is a promising therapeutic approach for wound disinfection, which employs controllable light to activate photocatalysts and generate reactive oxygen species (ROS) for the destruction of bacteria. However, preventing bacterial growth and overcoming the difficulty in wound healing after stopping the excitation are the main challenges in APCT. Herein, a new antibacterial photocatalyst, LiLuGeO4 :Bi 3+ /TiO2 (LGG/T), with persistent APCT activity was synthesized by loading titanium dioxide (TiO2 ) on the surface of an ultraviolet (UV) persistent luminescent material, LGG. After excitation by a 254 nm UV lamp, UV persistent luminescence (PersL) (∼350 nm) from LGG is efficiently absorbed by TiO2, which drives TiO2 to continuously produce ROS. In vitro antibacterial assay results show that LGG/T kills and inhibits the growth of the gram-negative and gram-positive bacteria surviving after stopping the excitation, owing to its continuous ROS generation ability. Furthermore, thermo-responsive hydrogel-loaded LGG/T (H@LGG/T) with sol–gel transition ability at body temperature was prepared and used for the treatment of bacteria-infected wounds. Because of the persistent antibacterial ability of LGG/T, H@LGG/T effectively promoted wound repair in mice with Staphylococcus aureus -infected dermal wounds, while demonstrating appropriate biosafety. Thus, H@LGG/T shows great potential for use in persistent wound disinfection. Highlights: A new antibacterial photocatalytic material LGG/T was reported and exhibits persistent catalytic activity. LGG/T exhibits antibacterial effect under UV light excitation as well as persistent antibacterial ability after excitation. Thermo-responsive hydrogel-loaded LGG/T was synthesized and applied in wound treatment.